Vertical stratigraphic variations and sedimentation model of the Lower Siwalik sequence in Kumaun Himalaya, India - Shukla, UK; Bora, DS (Himalayan Journal of Sciences, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> DOI = 10.3126/hjs.v5i7.1324 Himalayan Journal of Sciences Vol.5(7) (Special Issue) 2008 p.143